The Gatekeeping System on Restriction of Worship in The Mosque During Covid-19 on iNews.id - Thalitha Sacharissa Rosyiidiani (Universitas Muhammadiyah Prof. DR. Hamka, 2022)
The emergence of the COVID-19 pandemic has become a hotly discussed issue in various parts of the world, including Indonesia. Global issues and impacts on many people's lives have caused all media to share information related to the development of COVID-19, both mainstream and online media. The speed of online media in reporting information becomes a reference for citizens to know developments in real-time. One of the online media that consistently informs the public regarding the Covid-19 outbreak is iNews.id. In producing and presenting news, the media cannot be separated from the gatekeeping process before the news is published. This study aims to determine how iNews.id's gatekeeping efforts are in the production process of the COVID-19 pandemic issue. The use of gatekeeping theory is interesting to study because of its relevance to the current media situation, especially in the midst of a crisis when the public becomes very dependent on reporting in the media. Researchers analyzed using five levels of influence on the gatekeeping process in the online media iNews.id. The results of this study indicate that the factors that affect the way iNews.id in the production process of news on restrictions on worship in mosques due to the COVID-19 pandemic are the individual media worker level, the media routine level, the organizational level, the extra-media level, and the social system level. This study concludes that the most dominant levels in the gatekeeping process are the organizational level and the media routine level at iNews.id.